Sex and death on the western emigrant trail : the biology of three American tragedies - Grayson, Donald K. (University of Utah Press, 2018)
"During the winter of 1846-1847, members of the Donner Party found themselves stuck in the snows of the Sierra Nevada on their journey to California, losing many in their group to severe cold and starvation. Those who survived did so by cannibalizing their dead comrades. Today the Donner Party may be the most famous group of American overland emigrants to struggle through life-threatening conditions, but it is not the only one. Ten years after the Donner Party got itself into trouble, two groups sponsored by the Mormon Church ran into similar difficulties. Unlike the Donner Party, these people were following a well-traveled path, but they were doing it in a novel way, pushing and pulling their goods and children in handcarts some 1,300 miles from Iowa to Utah. In the end, over 200 died along the trail. The plights of these travelers have been addressed by different historians in different ways. This book is the first to examine these tragedies in terms of biology. Grayson shows that who lived and who died within these westward-bound groups can largely be explained by age, sex, and family ties. His investigation reveals what happens when our cultural mechanisms for dealing with famine and extreme cold are reduced to only what our very bodies can provide. These were real people in real danger. Understanding what happened to them helps us get at the core of who and what we all are"--Provided by publisher